Biogas Energy From Family-Sized Digesters In Uganda: Critical Factors And Policy Implications - Walekhwa, Peter N.; Mugisha, Johnny; Drake, Lars (Energy policy, 2009)
Dependence on fossil energy sources is increasingly becoming unsustainable due to ecological and environmental problems and rapid depletion. Biogas energy could augment these conventional energy sources but despite its advantages and favourable conditions for its production, biogas energy use in Uganda remains low due to technical, economic and socio-cultural impediments. Based on primary data on households in Central and Eastern Uganda and the use of logistic regression, this study analyses factors affecting the adoption of biogas energy in Uganda. The empirical results suggest that the probability of a household adopting biogas technology increases with decreasing age of head of household, increasing household income, increasing number of cattle owned, increasing household size, male head of household and increasing cost of traditional fuels. In contrast, the likelihood of adoption decreases with increasing remoteness of household location and increasing household land area. Policy options and recommendations including educational and awareness campaigns on biogas benefits and successes, the provision of financial and non-financial incentives to households and establishment of an institutional framework could bolster wider biogas energy acceptance in Uganda.
Keywords: Biogas energy; Family-sized digester; Uganda